Developing a Competitive Strategy Canvas for MSMEs: A Conceptual Framework Approach - Maya Malinda; Yolla Margaretha; Elizabeth Wianto (International Journal of Entrepreneurship, Business, and Creative Economy, 2026)
Micro, Small and Medium Enterprises (MSMEs) face increasing challenges in sustaining competitiveness due to limited strategic capabilities, inadequate competitor analysis, and insufficient differentiation strategies. Existing strategic tools are generally designed for large enterprises and often fail to address the specific characteristics and resource limitations of MSMEs. This study addresses the research gap by developing an integrated strategic framework to support MSMEs in building sustainable competitive strategies. The purpose of this strategy is to address the challenges faced by MSMEs and develop competitive strategies. The methodology of this strategic tool is qualitative, using a literature review of journals conducted with PRISMA 2020. The result is Competitive Strategy Canvas has eleven elements consisting of Focus on a niche market (F); Operationally efficient (O); Market Research & Analysis (R); Monitor and benchmark performance (M); Agile and Responsive (A); Invest in talent and training (T); Build Strong Customer Relationships (B); Sustainable Innovation (I); Differentiation (D); Effective Marketing and Branding (E); Strategic partnerships and alliances (S). Expectantly, the originality of this study lies in proposing a comprehensive strategic framework specifically designed for MSMEs, which may assist business owners in developing more adaptive and sustainable competitive strategies while also providing a foundation for future quantitative validation studies.